2019
DOI: 10.1002/adsc.201900605
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Synthesis of Six‐Membered P,O‐Heterocycles via Hydration/Intramolecular Cyclization Cascade Reaction

Abstract: Herein, we report the synthesis of sixmembered P,O-heterocycles from dialkynylphosphine oxides. By using gold(I) complexes, the chemoselectivity of the reaction was switched from literature-reported double hydration to a hydration/ intramolecular cyclization cascade. Control experiments indicated that the first alkyne hydration product is an intermediate of the reaction. In addition, a density functional theory (DFT) calculation allowed to rationalize the observed chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Tertiary amine substituted 3-en-1-yne was treated with anilines in presence of 5 mol% gold-catalyst, 10 mol% CF 3 SO 3 H in Wang's group described the synthesis of six-membered P, O-heterocycle scaffold 115 from di-alkynyl phosphine oxides 116 (Scheme 45). [84] For this purpose, the optimal reaction conditions were 5 mol% IPrAuCl, 1,2-dichloroethane as a solvent, 80 °C for 16 h treatment. This gold(I)-catalyzed chemoselective approach followed two key steps: hydration and followed by an intermolecular cyclization cascade reaction.…”
Section: Double Cascade Reactionsmentioning
confidence: 99%
“…Tertiary amine substituted 3-en-1-yne was treated with anilines in presence of 5 mol% gold-catalyst, 10 mol% CF 3 SO 3 H in Wang's group described the synthesis of six-membered P, O-heterocycle scaffold 115 from di-alkynyl phosphine oxides 116 (Scheme 45). [84] For this purpose, the optimal reaction conditions were 5 mol% IPrAuCl, 1,2-dichloroethane as a solvent, 80 °C for 16 h treatment. This gold(I)-catalyzed chemoselective approach followed two key steps: hydration and followed by an intermolecular cyclization cascade reaction.…”
Section: Double Cascade Reactionsmentioning
confidence: 99%
“…15 Herein, we report the gold(I)- catalyzed pathway-switchable tandem hydration-oxacyclization to 4-pyranones and 3(2H)-furanones from skipped diynones. 16 We selected symmetric diynone 2a as a model substrate for attempting the proposed hydration−cyclization reaction. After having assayed a variety of Lewis acids, we found that only gold(I) complexes 17 possess significant activity for the planned sequence using dioxane as solvent.…”
mentioning
confidence: 99%